Overexpression of Catalase Enhances Benzo(a)pyrene Detoxification in Endothelial Microsomes - Yang, Fang (PLoS One, 2016)
We previously reported that overexpression of catalase upregulated xenobiotic- metabolizing enzyme (XME) expression and diminished benzo(a)pyrene (BaP) intermediate accumulation in mouse aortic endothelial cells (MAECs). Endoplasmic reticulum (ER) is the most active organelle involved in BaP metabolism. To examine the involvement of ER in catalase-induced BaP detoxification, we compared the level and distribution of XMEs, and the profile of BaP intermediates in the microsomes of wild-type and catalase transgenic endothelial cells. Our data showed that endothelial microsomes were enriched in cytochrome P450 (CYP) 1A1, CYP1B1 and epoxide hydrolase 1 (EH1), and contained considerable levels of NAD(P)H: quinone oxidoreductase-1 (NQO1) and glutathione S-transferase-pi (GSTP). Treatment of wild-type MAECs with 1μM BaP for 2 h increased the expression of microsomal CYP1A1, 1B1 and NQO1 by ~300, 64 and 116%, respectively. However, the same treatment did not significantly alter the expression of EH1 and GSTP. Overexpression of catalase did not significantly increase EH1, but upregulated BaP-induced expression of microsomal CYP1A1, 1B1, NQO1 and GSTP in the following order: 1A1>NQO1>GSTP>1B1. Overexpression of catalase did not alter the distribution of each of these enzymes in the microsomes. In contrast to our previous report showing lower level of BaP phenols versus BaP diols/diones in the whole-cell, this report demonstrated that the sum of microsomal BaP phenolic metabolites were ~60% greater than that of the BaP diols/diones after exposure of microsomes to BaP. Overexpression of catalase reduced the concentrations of microsomal BaP phenols and diols/diones by ~45 and 95%, respectively. This process enhanced the ratio of BaP phenol versus diol/dione metabolites in a potent manner. Taken together, upregulation of phase II XMEs and CYP1 proteins, but not EH1 in the ER might be the mechanism by which overexpression of catalase reduces the levels of all the BaP metabolites, and enhances the ratio of BaP phenolic metabolites versus diol/diones in endothelial microsomes.